Thromboelastometry and organ failure in trauma patients: a prospective cohort study - Müller, Marcella CA; Balvers, Kirsten; Binnekade, Jan M; Curry, Nicola; Stanworth, Simon; Gaarder, Christine; Kolstadbraaten, Knut M; Rourke, Claire; Brohi, Karim; Goslings, J Carel; Juffermans, Nicole P (Critical care (London, England), 2014)
Introduction Data on the incidence of a hypercoagulable state in trauma, as measured by thromboelastometry (ROTEM), is limited and the prognostic value of hypercoagulability after trauma on outcome is unclear. We aimed to determine the incidence of hypercoagulability after trauma, and to assess whether early hypercoagulability has prognostic value on the occurrence of multiple organ failure (MOF) and mortality. Methods This was a prospective observational cohort study in trauma patients who met the highest trauma level team activation. Hypercoagulability was defined as a G value of ≥11.7 dynes/cm 2 and hypocoagulability as a G value of <5.0 dynes/cm 2 . ROTEM was performed on admission and 24 hours later. Results A total of 1,010 patients were enrolled and 948 patients were analyzed. Median age was 38 (interquartile range (IQR) 26 to 53), 77% were male and median injury severity score was 13 (IQR 8 to 25). On admission, 7% of the patients were hypercoagulable and 8% were hypocoagulable. Altogether, 10% of patients showed hypercoagulability within the first 24 hours of trauma. Hypocoagulability, but not hypercoagulability, was associated with higher sequential organ failure assessment scores, indicating more severe MOF. Mortality in patients with hypercoagulability was 0%, compared to 7% in normocoagulable and 24% in hypocoagulable patients ( P <0.001). EXTEM CT, alpha and G were predictors for occurrence of MOF and mortality. Conclusions The incidence of a hypercoagulable state after trauma is 10% up to 24 hours after admission, which is broadly comparable to the rate of hypocoagulability. Further work in larger studies should define the clinical consequences of identifying hypercoagulability and a possible role for very early, targeted use of anticoagulants.